Meio de Vida: Caminho da Morte - Almeida, Jaime (T.E.X.T.O.S DE H.I.S.T.Ó.R.I.A. Revista do Programa de Pós-graduação em História da UnB., 2011)
MILLER, Joseph C. Way of Death. Merchant Capitalism and the Angolan Slave Trade. 1730-1830. Madison. The University of Wisconsin Press. 1988.